2018
DOI: 10.1016/j.diagmicrobio.2018.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 4 commercially available group B Streptococcus molecular assays using remnant rectal–vaginal enrichment broths

Abstract: The incidence of neonatal Group B streptococcal (GBS) disease has significantly declined since the widespread implementation of prenatal screening of expectant mothers for urogenital and gastrointestinal tract GBS colonization. Screening methods have evolved from exclusively culture-based approaches to more rapid and highly sensitive molecular methods. We chose to evaluate the performance of 4 commercially available GBS molecular tests for detection of GBS colonization using 299 antepartum rectal-vaginal speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…In our study, the agreement among Panther Fusion, Aries and Xpert GBS assays was >97%. Another study found a 97% agreement between four NAATs (BD Max, Illumigene, Aries, and Xpert) (14). The results of this and other studies highlight the underestimation of GBS colonization with broth-enriched culture methods and support the adoption of NAATs as the new gold standard to improve GBS detection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the agreement among Panther Fusion, Aries and Xpert GBS assays was >97%. Another study found a 97% agreement between four NAATs (BD Max, Illumigene, Aries, and Xpert) (14). The results of this and other studies highlight the underestimation of GBS colonization with broth-enriched culture methods and support the adoption of NAATs as the new gold standard to improve GBS detection.…”
Section: Discussionmentioning
confidence: 99%
“…Several Food and Drug Administration (FDA)-cleared real-time PCR-based NAATs are currently available for the qualitative detection of GBS in enriched broth cultures. NAATs on sample-to-answer platforms offer standardized processing technology for specimen extraction, amplification, and detection, provide a shorter turnaround time to result, and demonstrate improved GBS detection rates compared to those of culture (1323).…”
Section: Introductionmentioning
confidence: 99%
“…Singleplex assays detecting GBS have also been developed, although many of these are optimised for identifying the bacterium from gut or vaginal colonisation and/or shortly after labour rather than for the diagnosis of acute infection [39,40]. Four commercial assays are available: (i) The Becton Dickinson MAX GBS assay; (ii) The ARIES GBS assay from Luminex Corporation; (iii) The Illumigene Group B Streptococcus assay from Meridian Bioscience; and (iv) The Xpert GBS LB assay produced by Cepheid Inc. Three of these use rtPCR assays, while Illumigene uses a loop-mediated isothermal amplification (LAMP) assay with the cfb gene as the primary target.…”
Section: Streptococcus Agalactiaementioning
confidence: 99%
“…Four commercial assays are available: (i) The Becton Dickinson MAX GBS assay; (ii) The ARIES GBS assay from Luminex Corporation; (iii) The Illumigene Group B Streptococcus assay from Meridian Bioscience; and (iv) The Xpert GBS LB assay produced by Cepheid Inc. Three of these use rtPCR assays, while Illumigene uses a loop-mediated isothermal amplification (LAMP) assay with the cfb gene as the primary target. The gene cfb encodes the extracellular pore-forming toxin also known as the CAMP factor [40]. The Christie-Atkinson-Munch-Peterson (CAMP) test has been the conventional culture-based test for identifying GBS and differentiates haemolytic versus non-haemolytic GBS.…”
Section: Streptococcus Agalactiaementioning
confidence: 99%
“…Culture-based methods remain the gold standard for GBS detection; however, numerous studies have suggested molecular methods, such as PCR, are more sensitive and specific compared to culture and represent a point-of-care detection option (El Helali et al 2009;de-Paris et al 2011;Khalil et al 2017;Wollheim et al 2017;Relich et al 2018). Cost-effectiveness is another consideration when evaluating screening methods, particularly in GBS where universal screening is implemented (Kaambwa et al 2010).…”
Section: Introductionmentioning
confidence: 99%